Finland : Staff Report for the 2012 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The paper is an account of Finland's unexpected upcoming deceleration in the economy at the end of 2011 and later. The deleveraging of the financial sector and the debt crisis made the nation fear an inevitable recession. To sustain this vulnerable situation, due attention was given to short-term growth and long-term challenges. Banks were encouraged to build up capitals and toughen bank decrees. Plans were made to multiply labor power and productivity. At the end of the paper, the Board welcomed the commitment of the state in improving and safeguarding the financial sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet